Pertanggungjawaban Notaris Dan Kepastian Hukum Penyelesaian Sengketa Kepemilikan Hak Atas Tanah Oleh Orang Asing Akibat Perjanjian Nominee - Kadek Mery Herawati (Jurnal Yustitia, 2021)
Nominee agreements are categorized as agreements that indicate creating legal smuggling. The Nominee Agreement has not yet been regulated in the Civil Code. The Nominee Agreement was made to provide an opportunity / gap for foreigners to control and own parcels of land in Indonesia. Nominee agreements between foreigners and Indonesian citizens relating to land ownership, cannot be separated from the role of a notary / PPAT. In practice, most foreigners and citizens use the services of a notary / PPAT to legalize the Nominee agreement. The objective to be achieved in this study is to provide legal understanding to the public regarding the Notary's Liability for the Nominee Agreement Making and the legal certainty of resolving disputes over land rights under the Nominee Agreement. Legal issues studied, namely: reviewing the Notary Liability arrangements in the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position (UUJN), was assessed using the Juridical-Normative research method. The results of this study indicate that: the responsibility of a Notary who acts against the Law through a Nominee agreement, does not set clear and strict sanctions in the form of civil sanctions or criminal sanctions in the UUJN. Settlement of disputes over nominee agreement matters is generally resolved through legal channels, namely through court proceedings because it involves contractual legal issues. However, other than through the Court (Litigation) and Non-Litigation (Non Litigation).